Study of bio-grout treated slope models under simulated rainfall - Omar R.C.; Taha H.; Roslan R.; Baharudin I.N.Z. (GEOMATE International Society, 2023)
Previous data reported that soil erosion in Malaysia was directly related to rainfall trends. This phenomenon could affect the overhead transmission towers which are at risk of collapsing due to slope failure. For soil stabilization, chemical grouting such as cement, lime and acrylamides were generally applied to enhance the physical properties of the soil. However, some of the chemical additives used in the grouting suspension may be toxic and hazardous to both humans and the environment. Thus, it is important to look for alternative grouting substances that are safe and sustainable. Recently, a new soil improvement technique based on carbonate precipitation by microbial activities from vegetable waste has been developed as bio-grout. This study was aimed to investigate the effectiveness of bio-grout from the vegetable waste in reducing soil loss due to rainfall impact. Soil samples were collected from an eroded slope nearby a transmission line in Perak and molded into 45 slope models in a custom-made box. A simple rainfall simulation was performed on the untreated and treated soil samples mixed with bio-grout for 30 days. The results showed that the soil loss of treated samples has been significantly reduced from 34.6 g to 13.5 g. Scanning electron microscopy showed aggregated particles occupying the empty spaces of the treated soils. Evidence of bio-mediated microbial activity was indicated by the presence of microorganisms in the bio-grout liquid. The bio-grout from vegetable waste proved to be an effective and eco-friendly new grouting material for soil erosion control.